A Linear Algorithm for Bipartite Drawing with Minimum Edge Crossings of Complete Binary Trees. - Albacea, Eliezer A. (Philippine Computing Journal)
In this paper, we present a simple linear algorithm for bipartite drawing with minimum edge crossings of complete binary trees. Also obtained with the drawing algorithm is the formula for computing the bipartite crossing numbers of complete binary trees